Accounting Workbook for QuickBooks 2003 - Fischer, Carol (South-Western, 2005)
Installing the quickbooks data files, Entries for the non-accountant Instructions for solving selected problems using quickbooks software chapters 2-3, Instructions for solving selected problems using quickbooks software chapters 4-16, Instructions for solving selected problems using quickbooks software special Journals Chapters 11 and 12, Instructions for solving selected problems using quickbooks software chapters 17-29, Setting up a new company, Demonstration problem solutions...